Innovations for community services : 19th International Conference, I4CS 2019, Wolfsburg, Germany, June 24-26, 2019, Proceedings /: 19th International Conference, I4CS 2019, Wolfsburg, Germany, June 24-26, 2019, Proceedings. ([2019]) - Unknown
No abstract available